Pregnancy and Care practices Gestación y prácticas de cuidado - ARÉVALO SÁNCHEZ ELIZABETH (Universidad Nacional de Colombia, 2007)
The purposeofthisresearch istovalue thecarepractices that mothers perform on themselves and on the baby to whom she is going to give birth. 150 pregnant women that go to the Centro Operativo Local Engativá medical facility, registered on project 7317: "Preganant Families: healthy and desired babies of the Administrative DepartmentofSocialWellbeing", using a quantitative and descriptive methodology. We applied the "Instrument to value those care practices that are performed on themselves and on the baby to whom they are going to give birth during the prenatal stage", It was carried out by research nurses of the Nursing Faculty at the Universidad Nacional de Colombia (1), and the data were analized in a descriptive manner by frequency and percentages. The results were obtained via a six dimension analysis that constitute the instrument where one identifies and characterizes the care practice. We conclude that in the pregnant group there is a regular care practice in the dimensions of : prenatal estimulation (56,67%), exercise and rest (78%), feeding paterns (82,67%) and good care practice in terms of hygine and personal care (88%), support systems (82%) and none beneficial substances (78,67%). La presente investigación tiene como objetivo valorar las prácticas de cuidado que realizan, consigo mismas y con el hijo por nacer, 150 gestantes que asisten al Centro Operativo Local Engativá, inscritas en el proyecto 7317: "Familias gestantes: bebés sanos y deseados del Departamento Administrativo de Bienestar Social", utilizando una metodología cuantitativa y descriptiva. Se aplicó el "Instrumento para valorar las prácticas de cuidado que realizan consigo mismas y con el hijo por nacer las mujeres en la etapa prenatal", desarrollado por enfermeras investigadoras de la Facultad de Enfermería de la Universidad Nacional de Colombia (1), y los datos se analizaron de manera descriptiva por medio de frecuencias y porcentajes. Los resultados se obtuvieron mediante el análisis de seis dimensiones que forman el instrumento donde se identifican y caracterizan las prácticas de cuidado. Se concluye que en el grupo de gestantes hay una regular práctica de cuidado en las dimensiones de: estimulación prenatal (56,67%), ejercicio y descanso (78%), alimentación (82,67%) y buena práctica de cuidado en higiene y cuidados personales (88%), sistemas de apoyo (82%) y sustancias no beneficiosas (78,67%).